An analysis of Kinesio® Tape on mitigation of dynamic knee valgum - Smedley, K. E. (North Dakota State University of Agriculture and Applied Science, 2022)
Kinesio® Tape has potential to be an intervention to mitigate dynamic knee valgum. This research project investigated the effect of Kinesio® Tape has on dynamic knee valgum through three-dimensional (3D) motion analysis in females with a history or current participation in competitive basketball or volleyball. Thirty volunteers preformed a Y-Balance test and drop jump landing (DJL) test with three different taping conditions. No tape, Kinesio® Performance Plus Tape for the facilitative gluteus medius application, and Kinesio® Tex Classic Tape for the spiral technique (ST). Results observed a statistically significant decrease in knee abduction valgum angle during 100 ms after initial contact on a DJL with application of the Kinesio® spiral technique. No significant results were observed between all three conditions during Y- Balance testing. Based off these findings we can conclude that applying the Kinesio® spiral technique mitigates dynamic knee valgum, therefore possibly decreasing the risk for ACL injury in females.